When a Lump Is Not a Cyst: A Case of Superficial Venous Aneurysm of the Hand Diagnosed with High-Resolution Ultrasound - Antonio Corvino; Orlando Catalano; Corrado Tagliati; Giulio Cocco; Domenico Tafuri; Fabio Corvino; Marco Fogante; Oriana Simonetti (Diagnostics, 2025)
Superficial venous aneurysms of the upper extremities are a rare clinical entity, often underdiagnosed and misinterpreted as other soft tissue masses. We present the case of a 28-year-old male patient with a subcutaneous mass on the dorsum of the left hand, diagnosed as a superficial venous aneurysm by high-resolution ultrasound using a probe bandwidth of up to 18 MHz, unchanged at three-month Doppler-ultrasound examination. This case highlights the fundamental role of high-frequency ultrasound in the differential diagnosis and conservative management of such lesions.